The role of health literacy in explaining regional health differences among adolescents. (13th November 2019) - Simonsen, N; Wackström, N; Roos, E; Suominen, S; Välimaa, R; Tynjälä, J; Paakkari, L
Abstract: Background: Health disparities in adolescence track forward to adulthood. In understanding disparities better, health literacy (HL) - as a broad range of health-related competencies - has been identified as a valuable construct. Higher HL has been associated with better health outcomes, also among adolescents. Not much is known about how language or region in a bilingual country is associated with HL, or how HL is associated with regional health disparities. The aim of this study, in a bilingual country, was a) to examine and compare HL and health levels among majority and minority language speaking adolescents in different regions of Finland, and b) to explore if HL explains possible regional health differences in these two language groups, taking into account other important structural stratifying factors. Methods: The data of 13- and 15-year-olds were obtained from the Health Behaviour in School-aged Children study, conducted in Finnish- and Swedish-speaking schools in Finland in 2014 (N = 3853/1123; 85/83%). HL was measured with the HLSAC-instrument. The data were analysed by logistic regression and interaction analyses. Results: In the total sample, 23% rated their health as excellent; 33% had a high and 10% a low HL. The preliminary findings showed no differences in health or HL between the language groups. However, regional health differences were found in both language groups: in the Finnish-speaking sample among boys, and in the Swedish-speaking sample among girls. Findings also showed regional differences in HL levels in both language groups, especially among the Swedish-speaking minority group. Comprehensive HL was an independent factor in explaining these regional health differences. Conclusions: This study adds to prior studies on the role of HL as a modifiable health resource by showing that in addition to other structural stratifying factors comprehensive HL explains regional health disparities among adolescents in a bilingual country. Key messages: This study in a bilingual country found regional health disparities and regional differences in HL levels among both majority and minority language speaking adolescents. In both language groups, taking into account other important structural stratifying factors, comprehensive HL was an independent factor in explaining the regional health differences.